A Comprehensive Approach To Alloplastic Cranioplasty: Novel Implant Design And Refinement of Soft Tissue Management. Issue 1 (March 2022) - O'Connor, Kaylee; Holan, Cole; Choudhary, Nikita; Curry, Eileen; Harshbarger, Raymond
Background: Large scale craniectomy defects are commonly reconstructed with alloplastic implants, which can restore brain protection and promote cosmesis. However, esthetic outcomes can be subpar due to skin contour abnormalities and temporal hollowing. Herein we describe a senior craniofacial surgeon's experience using a custom composite polyetheretherketone (PEEK) and porous polyethylene (Medpor) implant for alloplastic cranioplasty.Methods: A retrospective review was conducted of all PEEK-Medpor cranioplasty cases performed over the past 2 years. Patient characteristics, intraoperative information, surgical outcomes, and cosmetic outcomes were reviewed.Results: Sixteen patients (18-70 years of age) underwent surgery. Indications for cranioplasty included craniectomy due to trauma, stroke, or tumor, and bone resorption after a prior autologous cranioplasty. Augmentation of the temporalis area using alloderm or a muscle graft was performed in 7 cases. There were no intraoperative complications. Ultimately, all implants were maintained. One implant was temporarily removed due to infection, but successfully replaced. Three minor complications occurred. At an average follow-up of 9 months, 93.8% of surgical sites showed no significant temporal hollow.Conclusion: We describe a series of 16 implants using a composite PEEK Medpor implant for alloplastic cranioplasty, which resulted in a low infection rate and improved postoperative regional contour. Use of this implant with suspension of the temporalis muscle is a new technique that may allow for better adherence of the temporalis muscle to its anatomic position, while still providing good brain protection.